157. Verification of high dose delivery in radiosurgery management of brain functional disorders. (December 2018) - Gallo, P.; De Martin, E.; Marchetti, M.; Fumagalli, M.L.; Ghielmetti, F.; Alhujaili, S.; Lerch, M.L.F.; Carrara, M.; Rosenfeld, A.B.; Fariselli, L.; Petasecca, M.
Abstract : Purpose: The purpose of this study is to validate the use of an innovative detector (edgeless-diode)[1] to measure the dose delivered in stereotactic radiosurgery for brain functional disorders. Methods: Three diodes were inserted in a Rando phantom in 'trigeminal', 8 mm cranial and 26 mm caudal positions. In the framework of a dose escalation protocol, a trigeminal target patient's plan was properly optimized. The diode coincident with the PTV-position was prescribed at doses respectively of 75, 100, 140 and 200 Gy in one single fraction. In the 75 Gy delivery case an EBT3 film was placed in correspondence with the caudal diode position and a prescription dose of 12 Gy was imposed in order to validate the diode's recorded value. After the escalation of the dose, quality-assurance (QA) verifications were also performed for three patient planes with different prescription doses and placing the central diode in correspondence with the trigeminal target. Finally, the dose values measured by the three diodes were compared to the planned ones. Results: The Rando plan and patient QA results are summarized in the following table. Comparison of the dose values from the edgeless-diode with EBT3 film shows a difference of −4.6%. Conclusions: The edgeless-diode detectors were employed to measure the dose distribution of a full trigeminal stereotactic treatment; they record values of the dose in the central part of the PTV within 4% of the planned value for seven different plans. The verification of the value corresponding to a caudal position of the Rando-plan scaled at 75 Gy by EBT3 films shows a difference smaller than 5% in comparison with the edgeless-diode. The edgeless-diode employment in functional treatments QA procedures seems promising.